Avaliação dos parâmetros metabólicos e renais dos filhotes jovens de ratas Wistar com hipertireoidismo: benefícios do Resveratrol - Oliveira, Fernanda Busnardo de (2021)
Endocrine disorders in pregnancy can program diseases in the offspring's adult life. It is known that hyperthyroidism is associated with an increase in oxidative stress and that Resveratrol (RSV) is a polyphenol with several beneficial actions in the body, including anti-inflammatory and antioxidant effects. Objective: To evaluate the effects of maternal RSV treatment, during pregnancy, on the young offspring of hyperthyroid Wistar rats. Methodology: The 30 day-old female pups were divided into the following groups: C (control: pups from mothers who received a vehicle solution via gavage during pregnancy), C + R (control + RSV: pups from mothers treated with RSV, at the dose 100 mg/kg, during pregnancy), H (hyperthyroidism: pups of mothers treated with hormone T4, at a dose of 250µg/kg, during pregnancy) and H + R (hyperthyroidism + RSV: pups of mothers treated with T4 hormone, at a dose of 250µg/kg, and RSV, at a dose of 100mg/kg during pregnancy). The maternal parameters evaluated were: body weight during pregnancy and at the end of lactation, and the measurements of T3 and T4, plasma creatinine and blood glucose. In the offspring, the following parameters were analyzed: T3 and T4 measurements, lipid profile (cholesterol and triglycerides), blood glucose and renal function (glomerular filtration rate or GFR and urinary protein excretion or EUP); body weight and relative weights of thyroid, liver, heart and kidney. Renal and thyroid morphometric and immunohistochemical analysis were also performed. Results: In the dams, there was an increase in T3 and T4 levels in group H, and a reversal in T3 increase in H + R females treated with RSV. In the offspring, there was a decrease in T3, T4 and triglycerides in group H, when compared to group C. The relative cardiac weight of these animals was lower when compared to group C + R. Female pups of hyperthyroid mothers also presented a decrease in GFR and an increase in positive PCNA cells in the tubulointerstitial compartment (TBI) of the renal cortex, an increase in the expression of glomerular α-SMA and in TBI, in addition to morphometric changes such as an increase in the glomerular tuff area and a reduction of the capsular space area. Regarding the offspring’s thyroid, several alterations were observed, such as reduction in the follicle area, as well as in the area and height of the follicular epithelium. Maternal RSV treatment attenuated most of the changes found in the offspring of hyperthyroid mothers. Conclusion: Maternal hyperthyroidism interfered with triglyceride metabolism, in addition to causing important renal and thyroid changes in the offspring, from a structural and functional point of view, but maternal treatment with RSV was able to mitigate these effects in the young offspring of Wistar rats.